The Role of Mediation and Multigroups Investigation in Analyzing Islamic Fintech Users Behaviour - Siti Nur Azizah; Izra Berakon (SMART Insight, 2025)
This study aims to analyze the influence of financial incentives and digital literacy on user loyalty, with satisfaction as a mediating variable, and to test the differences in influence between variables through multigroup analysis based on gender and region. The study used a quantitative approach with primary data obtained through questionnaires. The sample was determined by purposive sampling technique and included 140 respondents. The data was analyzed using the PLS-SEM method through the WarpPLS version 8 application. The results showed that financial incentives and digital literacy had a significant positive effect on loyalty, with satisfaction as a mediator. However, the influence of digital literacy on loyalty becomes weaker when mediated by satisfaction. Multigroup analysis showed no differences by gender, but there were differences in the effect of financial incentives on loyalty between urban and rural areas.